Avaliação do conforto em infraestruturas cicloviárias com base em irregularidade longitudinal, vibrações medidas por smartphones e percepções dos ciclistas - Lima Terceiro Neto, Antonio Dias de (2020)
The use of bicycles, as a means of transport, has been growing, and, therefore, it is important for the Government to expand and maintain cycling infrastructures in good conditions. Therefore, it is important periodically to carry out evaluations to identify the current condition and define intervention strategies, aiming to maintain an acceptable level of quality, because deteriorated roads can discourage bicycling. However, the literature shows that evaluations are predominantly subjective, depending strictly on opinion of evaluators, therefore there is a gap on objective evaluations for bicycle infrastructures. In this sense, this research aimed to use physical measures to assess comfort in bicycle infrastructure in a practical, reliable and low cost way. For this, roughness measurements of pavements were collected with the Machine for Evaluating Roughness Using Low-cost Instrumentation (MERLIN) equipment and vertical acceleration measures with pre installed applications in a smartphone fixed on a bicycle and, finally, a subjective evaluation was carried out with cyclists, dealing with comfort on cycling infrastructure. The statistical analyze carried out with collected data allowed an establishment of comfort scales in terms of the International Roughness Index (IRI) and the Root Mean Square (RMS), based on the perception of cyclists, making it possible to fit infrastructure evaluation in an interval between “Extremely uncomfortable” (0) and “Extremely comfortable” (5). There was a correlation between roughness, vibration and subjective evaluation with adjusted coefficient R² around 0.9; thus, rougher pavement causes greater vibrations and is more uncomfortable. It can be seen that cyclists do not tend to accept bicycle infrastructure with IRI above 6.74 m/km and with RMS above 3.1 m/s², values that can serve as a trigger for maintenance and rehabilitation interventions. Afterwards, the scales found with the method were applied to evaluate a stretch of bicycle path in the city of João Pessoa-PB, from which comfort maps were obtained, which allowed a better visualization of the current conditions of the bicycle path. Finally, it can be concluded that measures of roughness and vibration, and comfort maps can support the decision making of transport planners and administrators, regarding the interventions necessary to maintain the quality of ride for cyclists, and indirectly encouraging bicycling.